Local Wisdom As The Basic Of Analysis In The Planning Of The Management Of The Relationship Between School And Society - Asri Widiatsih; Nurul Ulfatin; Imron Arifin; Achmad Supriyanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The law of Indonesian Republic Number 20 year 2003 Chapter XIV article 50 verse 5 states that The local government manages the primary and secondary education and a unit of education on a local basis. The purpose of this study was to describe how local wisdom ethnic Madurese as the basic for analysis in planning of the management of the relationship between school with society to improve the quality of education. This research was conducted using qualitative approach using multi sites study. The activity in sites data analysis is done by data condensation, data display, and conclusion drawing/verification. Based on the research findings of the school which understands local wisdom as a way of dealing with things based on local culture as the basic of the analysis in the planning of the management of the relationship between school with society.